CODE SWITCHING UTTERANCES OF PUBLIC FIGURES’ VLOG IN YOUTUBE CHANNEL - Halimah Tussa'diah; Eka Anggaini; Selamat Husni Hasibuan (IKIP Siliwangi, 2021)
This research dealt with the analysis of Code-Switching Utterances of Public Figures’ Vlog In YouTube Channel. The objectives were to determine code-switching and the types of code-switching used by the public figures and the guests. The researcher focused on the application of Intra- sentential (74 cases), Inter-sentential (85 cases) and Extra/Tag code-switching (26 cases). A descriptive qualitative method was taken to analyze the data from four videos on YouTube published in March 2019 until November 2019. The finding showed that public figures and the guests used code-switching, which included 185 cases. There were seven reasons of public figures switched the language; 75 data of talking about a particular topic, 2 data of quoting somebody else, 1 data of being emphatic about something, 13 data of interjection (inserting sentence filler or sentence connector), 27 data of repetition of clarification, 63 data of intention for clarifying the speech content for the interlocutor, and 4 data of expressing group identity.